2018
DOI: 10.1159/000490948
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Pitch, Gender, and Prosodic Context on the Identification of Creaky Voice

Abstract: Rates of identifying creak in male and female speakers are similar, suggesting that listeners have a comparable ability to hear creaky voice in all speakers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 75 publications
1
10
0
Order By: Relevance
“…Much of this work is summarized in Kreiman, Gerratt, Garellek, Samlan, and Zhang (2014) and Garellek (2019), who lay out a psychoacoustic model of voice quality which contains four major components: harmonic source spectral slope, inharmonic source noise, time‐varying source characteristics, and the vocal tract transfer function. For spectral tilt in creaky phonation, low H1 − H2 (the amplitude of the first harmonic minus the amplitude of the second harmonic) relative to modal vowels has been shown to be a reliable acoustic correlate of the vocal fold constriction that characterizes most creaky phonation (Andruski & Ratliff, 2000; Blankenship, 2002; Brunelle & Finkeldey, 2011; Davidson, 2019a; DiCanio, 2012; Garellek, 2015; Garellek & Keating, 2011; Miller, 2007). In some languages, other spectral tilt measures may also distinguish creaky from modal phonation, such as H1 − A3 (the amplitude of the first harmonic minus the amplitude of the harmonic closest to F3) in Itunyoso Trique (DiCanio, 2012), H1 − A2 (the amplitude of the first harmonic minus the amplitude of the harmonic closest to F2) in Jalapa Mazatec (Garellek & Keating, 2011), or H2 − H4 (the amplitude of the first harmonic minus the amplitude of the fourth harmonic) in American English (Garellek & Seyfarth, 2016).…”
Section: Articulatory and Acoustic Properties Of Creaky Phonationmentioning
confidence: 99%
See 2 more Smart Citations
“…Much of this work is summarized in Kreiman, Gerratt, Garellek, Samlan, and Zhang (2014) and Garellek (2019), who lay out a psychoacoustic model of voice quality which contains four major components: harmonic source spectral slope, inharmonic source noise, time‐varying source characteristics, and the vocal tract transfer function. For spectral tilt in creaky phonation, low H1 − H2 (the amplitude of the first harmonic minus the amplitude of the second harmonic) relative to modal vowels has been shown to be a reliable acoustic correlate of the vocal fold constriction that characterizes most creaky phonation (Andruski & Ratliff, 2000; Blankenship, 2002; Brunelle & Finkeldey, 2011; Davidson, 2019a; DiCanio, 2012; Garellek, 2015; Garellek & Keating, 2011; Miller, 2007). In some languages, other spectral tilt measures may also distinguish creaky from modal phonation, such as H1 − A3 (the amplitude of the first harmonic minus the amplitude of the harmonic closest to F3) in Itunyoso Trique (DiCanio, 2012), H1 − A2 (the amplitude of the first harmonic minus the amplitude of the harmonic closest to F2) in Jalapa Mazatec (Garellek & Keating, 2011), or H2 − H4 (the amplitude of the first harmonic minus the amplitude of the fourth harmonic) in American English (Garellek & Seyfarth, 2016).…”
Section: Articulatory and Acoustic Properties Of Creaky Phonationmentioning
confidence: 99%
“…Some harmonics used in spectral tilt measurements are illustrated in Figure 1. As for inharmonic noise, measures such as cepstral peak prominence, harmonics‐to‐noise ratio (HNR), and jitter have shown that creaky voice is usually less periodic than modal voice (Blankenship, 2002; Davidson, 2019a; Garellek, 2012; Garellek & Keating, 2011; Kuang & Liberman, 2016). One consideration regarding measures relying on F0 is that if creaky phonation causes the fundamental frequency to be too aperiodic to be accurately tracked, then it is not possible to correctly estimate spectral tilt or noise measures that are based on harmonics.…”
Section: Articulatory and Acoustic Properties Of Creaky Phonationmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly to HRT, this prosodic feature is often found at the end of utterances, or on pre-final syllables (Henton & Bladon: 1988). Creaky voice may be recognized aurally (Davidson: 2018) and observable on a spectrogram. This phonation type may also be identified by calculating jitter and shimmer values of a voice, which respectively refer to the variability of fundamental frequency, and variability of the amplitude of sound waves (Wertzner et al: 2005).…”
Section: 'Female' Prosodic Vulgarismsmentioning
confidence: 99%
“…The goals of the current paper are (a) to provide an update on the state of research since Gordon and Ladefoged's (2001) overview, maintaining their original focus on the acoustics of phonation as it is used for contrastive and allophonic purposes, and (b) to also expand further into studies of the perception of phonation, reflecting the considerable recent growth in that field. In the interest of space and in keeping with Gordon and Ladefoged's (2001) approach, we do not attempt to provide an extensive overview of the articulatory mechanisms involved in phonation (see Garellek, 2019a, 2019b; Kreiman & Sidtis, 2011; Laver, 1981), nor do we cover the many ways in which phonation is used as a marker of prosodic structure (Epstein, 2002; Redi & Shattuck‐Hufnagel, 2001), as an index of social factors (see Kreiman & Sidtis, 2011) such as gender (Davidson, 2019a, 2019b; Zimman, 2018; Becker, Khan, & Zimman, 2017; Podesva, 2013; Yuasa, 2010), sexual orientation (Podesva, 2007), or ethnicity (Szakay, 2012), or as a result of voice pathology (see Kreiman & Gerratt, 1996, 2005; Sapienza, Hicks, & Ruddy, 2011).…”
Section: Introductionmentioning
confidence: 99%